Political communication in the social network TikTok: experience of inter-party presidential consultations in Colombia 2022 - Lozano García, Mario Alexander (2022)
This article analyzes the political communication applied to the social network TikTok, digital scenario of electoral intervention in the inter-party consultations for the Colombian presidency 2022; for this purpose, a review of 19 TikTok videos that visualize or criticize the proposals of some candidates of the coalitions Equipo por Colombia, Pacto Histórico and Centro Esperanza is presented. During the study, it became evident that the latest social networks, mainly TikTok, had an electoral debut in attracting votes for the presidency, allowing some candidates to incorporate it within the strategies to promote political marketing. Likewise, theoretical models related to TikTok are examined, such as challenge videos, videos with special effects and music videos or montages; also eight categories of videos: video games, choreography or music videos, videos of conventional scenes, funny videos, event videos, tutorial videos, videos with animals and video selfies. The results obtained conclude on the intrinsic fusion between political communication and TikTok videos in the popular election debates in Colombia.